Społeczny pesymizm w prozie Romana Sienczina - Roman-Rawska, Katarzyna (Rusycystyczne Studia Literaturoznawcze, 2015)
The paper is an introduction to the problems of the contemporary works of a Russian writer Roman Senchin (born 1971). The author is considered to be a representative of the new realism current and his prose is a paradigmatic example of socially-oriented literature. Due to the sociological perspective, the article exposes social and political aspects of his work, but less attention has been paid to poetics as such. However, the psychological and existential aspect of Senchin’s work was also stressed. Furthermore, an attempt was made to resolve the dilemma, whether in relation to Senchin’s works it is relevant to use such theoretical concepts as politics of literature and politics in the literature.